Do housing options affect child birth decisions? Evidence from Taiwan. (December 2016) - Lin, Pei-Syuan; Chang, Chin-Oh; Foo Sing, Tien
This study aims to empirically test the effects of various housing options, which include renting, owning, living with parents/siblings, living in houses bought by parents and living in staff housing, on fertility decisions of families. This study uses micro-data obtained from the Taiwanese Panel Study of Family Dynamics (PSFD) surveys for the period from 1999 to 2007 to empirically test three hypotheses relating housing options to childbearing decisions. Using families living in rented houses as the control group, we find that homeowners have their first child at an older age, and families living with their parents or sibling become parents at a younger age. The results are robust and consistent after controlling for the district fixed effects and the marriage year fixed effects. We test the housing price shocks on the childbearing decisions for families who were married or bought houses during or after the housing boom period in 1987, and find that the asymmetric housing price effects on fertility decisions are correlated with the marriage event, but not the house purchase event.